Endobronchial Carcinoid Tumour with Extensive Ossification: An Unusual Case Presentation - Allison Osmond; Emily Filter; Mariamma Joseph; Richard Inculet; Keith Kwan; David McCormack (Case Reports in Medicine)
Carcinoid tumour is a well-known primary endobronchial lung neoplasm. Although calcifications may be seen in up to 30% of pulmonary carcinoid tumours, near complete ossification of these tumours is an unusual finding. Such lesions can prove diagnostically challenging at the time of intraoperative frozen section as the latter technique requires thin sectioning of the lesion for microscopic assessment. We present an unusual case of endobronchial carcinoid tumour with extensive ossification in a 45-year-old male. Preliminary intraoperative diagnosis was achieved through the alternative use of cytology scrape smears. The final diagnosis was confirmed after decalcification of the tumour. The prognostic implications of heavily ossified carcinoid tumours remain elusive. Long-term clinical follow-up of these patients is recommended.